Inadvertent Dural Puncture Causing Low Pressure Headache and Peripheral Vestibular Bilateral Damage - N. S. Longridge; A. I. Mallinson; R. G. Robinson (Audiology Research)
Introduction: This edition of the Audiology Research journal is dedicated to Dr. John Epley. For this reason, we would like to present a very unusual case involving the development of a bilateral abnormality of the otolith organs. The otoliths are the structures from which calcium particles detach to induce benign paroxysmal positional vertigo, the disorder for which Dr. Epley is famous for managing. Case report: This case report outlines an unusual presentation of vestibular pathology involving the otoliths. Discussion: We suggest that the atypical presentation may be related to a bilaterally asymmetrical insult to the otoliths. Conclusions: The central insult suffered by this patient resulted in bilateral peripheral otolithic pathology.